Functional analysis of fibrinogen-related proteins (FREPs, Ixoderins) of the tick Ixodes ricinus and their function in pathogen transmission - Hönig Mondeková, Helena (Jihočeská univerzita, 2016)
This study is focused on characterization of fibrinogen-related proteins (FREPs) from the tick Ixodes ricinus using molecular methods - PCR, cloning, qRT-PCR, RNA interference via dsRNA synthesis and injection, and also pathogen (Borrelia sp.) transmission on animal model.
Functional analysis of fibrinogen-related proteins (FREPs, Ixoderins) of the tick Ixodes ricinus and their function in pathogen transmission
Keywords: Fibrinogen-related proteins; Ixoderins; Ixodes ricinus; tick innate immunity; Fibrinogen-related proteins; Ixoderins; Ixodes ricinus; tick innate immunity